Two reciprocal translocations associated with microcephaly and retardation. Issue 2 (April 1977) - Bell, E F; Warburton, D
Abstract : The first case is reported of a karyotype containing two apparently unrelated reciprocal translocations, involving chromosomes 1, 2, 5, and 7. It is suggested that the patient's psychomotor retardation and microcephaly may be the result of the loss of a small amount of chromosomal material accompanying these translocations.